Study protocol for an individually randomized control trial for India's first roleplay-based mobile game for reproductive health for adolescent girls - Saha, Ananya; Dixit, Anvita; Shankar, Lalita; Battala, Madhusudana; Khan, Nizamuddin; Saggurti, Niranjan; Ayyagari, Kavita; Raj, Aparna; Howard, Susan (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Go Nisha Go™ (GNG), is a mobile game combining behavioural science, human-centric design, game-based learning, and interactive storytelling. The model uses a direct-to-consumer (DTC) approach to deliver information, products, services, interactive learning, and agency-building experiences directly to girls. The game’s five episodes focus on issues of menstrual health management, fertility awareness, consent, contraception, and negotiation for delay of marriage and career. The game’s effectiveness on indicators linked to these issues will be measured using an encouragement design in a randomized controlled trial (RCT). Methods A two-arm RCT will be conducted in three cities in India: Patna, Jaipur, and Delhi-NCR. The first arm is the treatment (encouragement) arm (n = 975) where the participants will be encouraged to download and play the game, and the second arm (n = 975) where the participants will not receive any nudges/encouragement to play the game. They may or may not have access to the game. After the baseline recruitment, participants will be randomly assigned to these two arms across the three locations. Participants of the treatment/encouragement arm will receive continuous support as part of the encouragement design to adopt, install the game from the Google Play Store at no cost, and play all levels on their Android devices. The encouragement activity will continue for ten weeks, during which participants will receive creative messages via weekly phone calls and WhatsApp messages. We will conduct the follow-up survey with all the participants (n = 1950) from the baseline survey after ten weeks of exposure. We will conduct 60 in-depth qualitative interviews (20 at each location) with a sub-sample of the participants from the encouragement arm to augment the quantitative surveys. Discussion Following pre-testing of survey tools for feasibility of methodologies, we will recruit participants, randomize, collect baseline data, execute the encouragement design, and conduct the follow-up survey with eligible adolescents as written in the study protocol. Our study will add insights for the implementation of an encouragement design in RCTs with adolescent girls in the spectrum of game-based learning on sexual and reproductive health in India. Our study will provide evidence to support the outcome evaluation of the digital mobile game app, GNG. To our knowledge this is the first ever outcome evaluation study for a game-based application, and this study is expected to facilitate scalability of a direct-to-consumer approach to improve adolescent sexual and reproductive health outcomes in India. Trial registration number: ctri.nic.in: CTRI/2023/03/050447.

Plain language summary Our paper describes implementation of a study protocol for an outcome evaluation of a mobile game app called Go Nisha Go™, produced by the Game of Choice, Not Chance™ project, funded by USAID. Consenting adolescent girls, aged 15–19, from three cities in India will be enrolled to participate in an encouragement design led RCT. Girls will be randomly assigned to either, a) a treatment (encouragement) arm where they will be nudged to play the game for ten weeks, or b) a control arm where participants will not be provided any encouragement to download or play the game. The study will be evaluated using surveys at baseline and follow-up. The findings from this study will support the measurement of effectiveness of the digital intervention and facilitate scalability of a direct-to-consumer approach, using a game-based application to improve adolescent sexual and reproductive health outcomes in India.